1995
DOI: 10.1111/j.1600-0536.1995.tb00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with skin irritation of the hands experienced by general dental practitioners

Abstract: Practising dental surgeons are now wearing gloves for longer periods of time than any other comparable group. As part of a study to assess dentists' attitudes to cross-infection, a questionnaire was sent to 1950 randomly selected general dental practitioners in England and Wales, with information being requested concerning the incidence of skin irritation of the hands considered to be associated with glove wearing. The response to the questionnaire was 61%, with 29% of respondents indicating that they experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
9
22
0
Order By: Relevance
“…18 Briefly, the gloves were filled S ince the mid-1980s, the wearing of gloves by dental healthcare workers (DHCWs) has been an essential element of dental surgery cross-infection control procedures. [1][2][3][4] Gloves may be punctured during use, with the incidence of puncture varying with different gloves and between operators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Briefly, the gloves were filled S ince the mid-1980s, the wearing of gloves by dental healthcare workers (DHCWs) has been an essential element of dental surgery cross-infection control procedures. [1][2][3][4] Gloves may be punctured during use, with the incidence of puncture varying with different gloves and between operators.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] In this respect, 6.2% of operating theatre staff have been shown to be hypersensitive to latex proteins, 11 as have 17% of hospital staff. 12 It has been considered that the wearing of latex gloves is not without risk to either dental clinician or patient.…”
mentioning
confidence: 99%
“…Around 15% of dentists reported hand eczema in a previous Swedish survey 62) . More than one fifth of dentists (22%) reported occupational contact dermatitis in a study from Thailand 12) , while one third of dentists reported symptoms of hand dermatoses during the previous 12 months in New Zealand 63) , UK 64) , and Queensland, Australia 65) . A study of dental hygienists in Norway also found similar results 9) .…”
Section: Dermatitis and Respiratory Hypersensitivitymentioning
confidence: 99%
“…In a Swedish study, about 15% of dentists reported hand eczema, in one Th ai study occupational CD was demonstrated in 22% of dentists, even more frequently in New Zealand (one-third of dentists reported hand dermatoses), also in Great Britain, in Queensland, Australia, as well as in Norway 2,[12][13][14] . As to sex distribution, occupational dermatoses are more common in women, as well as in younger and less experienced dentists [12][13][14] . It was also observed that dentists with a history of allergic conditions had a higher prevalence of hand dermatitis, as well as those with hobbies that include the use of solvents 2 .…”
Section: Prevalence Of Occupational Dermatosesmentioning
confidence: 99%